2018
DOI: 10.1039/c8ta01692e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal annealing reduces geminate recombination in TQ1:N2200 all-polymer solar cells

Abstract: Annealing of TQ1:N2200 photovoltaic blends reduces geminate charge recombination, without compromising charge extraction, leading to higher photocurrents and device efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 46 publications
5
61
0
Order By: Relevance
“…For the purpose of J-V simulation, we first measured the optical constants, namely, refractive index and extinction coefficient, of all active layers using ellipsometry ( Figure S3, Supporting Information). [36] Figure 2b shows that the simulated J-V curves (solid lines) closely resemble the experimentally measured J-V data (symbols). Rate constant values of ≈1 × 10 −12 cm 3 s −1 for PBDT(T)[2F]T-based cells, and ≈7 × 10 −12 cm 3 s −1 for PBDB-T-based device, were found to yield best fits between experiment and simulation.…”
Section: Resultssupporting
confidence: 56%
“…For the purpose of J-V simulation, we first measured the optical constants, namely, refractive index and extinction coefficient, of all active layers using ellipsometry ( Figure S3, Supporting Information). [36] Figure 2b shows that the simulated J-V curves (solid lines) closely resemble the experimentally measured J-V data (symbols). Rate constant values of ≈1 × 10 −12 cm 3 s −1 for PBDT(T)[2F]T-based cells, and ≈7 × 10 −12 cm 3 s −1 for PBDB-T-based device, were found to yield best fits between experiment and simulation.…”
Section: Resultssupporting
confidence: 56%
“…We have studied more materials with these combinations of transient spectroscopy and KMC, and found similar physics to rule in polymer/polymer blends [182] and in evaporated molecule/molecule blends. We have studied more materials with these combinations of transient spectroscopy and KMC, and found similar physics to rule in polymer/polymer blends [182] and in evaporated molecule/molecule blends.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 73%
“…It has moved rapidly, with a PCE of 3.3% in 2013, [238] 5.7% in 2014, [239] at 7.7% in 2015, [240,241] at 8% in 2016, [242] and 10% in 2017. [182] Clearly, the morphology of the blends influences photocurrent and fill factor. We found that thermal annealing of the spincoated blend can lead to improvement of the PCE by almost 2 times, to reach 4.4% PCE.…”
Section: Polymer/polymer Blendsmentioning
confidence: 99%
“…[15] This was attributed to dead ends where carriers need to hop against the direction of the field to escape the spatial trap and continue drift. [17] We tentatively associate spatial traps with chain ends that hamper the initial, short-range separation of the photocreated electron-hole pair, leading to strongly enhanced geminate recombination. Upon annealing the effect of these spatial traps largely vanishes.…”
Section: Introductionmentioning
confidence: 86%
“…In a broader perspective, these results highlight a morphological problem which may occur in all bulk-heterojunction OPVs, and show that relatively simple processing steps, such as thermal annealing, can possibly at least partly resolve the issue. [17] Figure 2a shows the dependence of the TDCF photocurrent kinetics on the collection delay time measured at close to zero effective generation voltage. Note that all voltages specified here and below are effective values that account for the applied voltage and the built-in potential U eff = U appl + V BI (V Bl = −0.47 V).…”
Section: Introductionmentioning
confidence: 99%